Physical Exercise to Improve the Balance of the Elderly with the Risk of Falling: a Literature Review - Anggraeni, Dwi Nur; Dewi, Arlina (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Most falling occurs in the elderly because of the decrease of balance and muscle strength. Physical training for elderly needs to conduct to enhance physical fitness of the elderly and it can reduce the risk of falls by increasing muscle strength by increasing body balance in the elderly. The aim of this research is to find out the effectiveness of physical exercise to improve balance in the elderly. Method to collect database is conducted in Google Scholar and Pubmed to find literature. Literature used was literature that required the inclusion criteria published in the last three years, then the result is chose and the review is conducted. Result: there are 6 literature to be reviewed. Based on literature review, it is found that respondents are 65-91 years old. Most respondents are elderly women.